Analysis of Factors Affecting Compliance Antiretroviral Treatment in HIV AIDS Patients - Farhan Imba; Nawang Wulan Nago Pita Sari; Ferdinta D Setyawan; Fitri Oktavia; Nur Annisa; Sendy Stefanie Longe; Eydrene Beatrix Hattu; Rizky Alfiana (Indonesian Journal of Global Health Research, 2026)
Human Immuno deficiency Virus / Acquired Immune Deficiency Syndrome (HIV / AIDS) can not be cured but this infection can be controlled with antiretroviral drugs (ARVs). Compliance of people with HIV/AIDS (PLWHA) is very important to cope with HIV/AIDS. Non-compliance with antiretroviral therapy gives the effect of drug resistance so that the drug cannot function or fail. The purpose of this study was to determine the factors that affect the compliance of antiretroviral therapy program in PLWHA in Puskesmas Harapan. The design of this study is cross sectional. The respondents of this study were PLWHA patients undergoing antiretroviral therapy program in infection health centers totaling 25 respondents determined by purposive sampling. The Data was collected with a uestionnaire heet and Pill Count. Analysis of the data using Pearson correlation test, spearman rho and multivariate logistic regression CI ③ = 0.05. The results showed that ARV treatment adherence is related to knowledge (p = 0.017), side effects (p=0.418) no relationship, and support taking medication (p = 0.278) conclusion drug side effects are the dominant factors affecting ARV therapy adherence.